2008
DOI: 10.1088/0953-8984/20/04/045221
|View full text |Cite
|
Sign up to set email alerts
|

New measurements of the coherent and incoherent neutron scattering lengths of13C

Abstract: The techniques of neutron interferometry and neutron diffraction were used to determine the coherent and incoherent neutron scattering lengths of 13 C. From a neutron interferometry measurement of the optical path difference in liquid samples, 13 CS 2 versus nat CS 2 , we obtain a bound coherent scattering length of b coh,13C = 6.542 ± 0.003 fm, which differs appreciably from the standard tabulated value of 6.19 ± 0.09 fm. The resulting contrast of only 0.106(3) fm with respect to b coh,natC = 6.6484 ± 0.0013 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…Extensive discussion of this point has been presented in Ref. 28. Since the coherent cross section of hydrogen is smaller by a factor of about 40 than the incoherent cross section the impact of the H impurity on the coherent signal is negligible.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Extensive discussion of this point has been presented in Ref. 28. Since the coherent cross section of hydrogen is smaller by a factor of about 40 than the incoherent cross section the impact of the H impurity on the coherent signal is negligible.…”
Section: Methodsmentioning
confidence: 99%
“…Unfortunately, in the course of this study it was found that the scattering contrast between the carbon isotopes is very small, substantially smaller yet than standard table values would suggest. 28 That makes the direct matrix inversion of the equation system used to determine the partial structure factors ill defined ͑see below͒. We rely on molecular dynamics simulations of molecules interacting through Lennard-Jones and electrostatic total potential models, seeking the optimal parameters leading to the best representation of the three independent scattering data sets.…”
Section: Introductionmentioning
confidence: 99%
“…The experimental procedure is described in Ref. [14] and the full details will be reported elsewhere [15]. The measured values of b17 O ¼ 5:867ð4Þ and b18 O ¼ 6:009ð5Þ fm were reproduced, within the experimental uncertainties, during two interferometry experiments performed a year apart.…”
mentioning
confidence: 99%
“…Rauch and Werner 2000). Our first interferometry experiment measured b coh for the 13 C isotope to high accuracy (Fischer et al 2008), giving a value that differed significantly from a previous standard value measured by Koester et al (1979). Our result not only explained a long-standing problem in NDIS experiments employing carbon isotope substitution, but provided an accurate scattering length value for 13 C that was used for a PSF analysis of the structures of liquid CS 2 and liquid CO 2 (Neuefeind et al 2009).…”
Section: Introductionmentioning
confidence: 63%